A systematic review of the clinical applications and complications of bone marrow aspirate concentrate in management of bone defects and nonunions - Imam, Mohamed A.; Pepke, Wojciech (International orthopaedics, 2017)
PurposeFracture healing encompasses a succession of dynamic multifactorial metabolic events, which ultimately re-establishes the integrity of the biomechanical properties of the bone. Up to 10% of the fractures occurring annually will need additional surgical procedures because of impaired healing. The aim of this article is to review the current literature regarding the use of bone marrow aspirate concentrate (BMAC) and its effectiveness in the management of bone defects.MethodsWe have included all published clinical literature investigating the development, techniques and applications of BMAC. Language, design and risk of bias did not deter the initial inclusion of any study. Our search was exclusively limited to studies involving human subjects. A PRISMA compliant search was carried out as published in 2009. This included the online databases: PubMed, EMBASE, clinical trial.gov and the Cochrane library from 1960 to the end of May 2015. MeSH terms used included: “Bone” AND “Marrow” AND “Aspirate” AND “Concentrate” AND “Bone Defects” AND “NONUNION”. Eligible studies were independently appraised by two authors using the Critical Appraisal Skills Program checklist. For the purpose of narrative review, relevant studies were included irrespective of methodology or level of evidence.ResultsThirty-four of the 103 (48 PubMed and 55 EMBASE) results yielded by the preliminary search were included. Exclusions included three duplicate records, six letters, 17 non-orthopaedics related studies and four records irrelevant to our search topic. The CASP appraisal confirmed a satisfactory standard of 31 studies. They all had clearly defined objectives, were well designed and conducted appropriately to meet them. The published studies reported the use of BMAC in non-union and fracture healing (15 studies), bone defects (nine studies), spine fusion (two studies), distraction osteogensis (two studies) and complications related to the use of BMAC (seven studies).ConclusionsStem cells found in BMAC have the potential to self-renew, undertake clonal expansion and differentiate into different musculoskeletal tissues. The commercial processing of BMAC needs to be optimized in order to achieve a consistent end product, which will provide predicable and translatable results. The future potential of cell characterization in order to determine the optimum cell for repair/regeneration of bone also needs to be explored. Level of Evidence: Systematic Review of minimum level IV studies.